Long term survival of antenatally diagnosed functionally single ventricle congenital heart disease. (25th January 2023) - Lim, J S L; Sutcliffe, D; Sabu, A; Ramaraj, R; Agarwal, U
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Antenatal diagnosis of single ventricle congenital heart disease (CHD) allows prenatal counselling, better parental preparation and support as well as improved perinatal management. Expectant parents frequently ask about likely outcomes and expected longer term survival. Our aim is to review the survival of antenatally diagnosed single ventricle CHD presenting at our institutions between January 2000 and July 2022. Methods: Retrospective data was collected from the fetal cardiac and paediatric cardiology databases. Maternal data, fetal cardiac diagnosis, postnatal cardiac diagnosis and management were collected for each patient. The outcomes were separated into 2 groups – Cohort 1 (CO1) [2000 to 2007] and Cohort 2 (CO2) [2008 to 2022]. Results: A total of 495 fetuses were diagnosed with single ventricle CHD in the 21 years and 7 months period, with outcomes illustrated in Table 1. For the small LV group with intention to treat at birth, there was 46% survival at over 10 years for the CO1 group and 69% survival at over 10 years for CO2 group. There was however no significant difference in the survival between the CO1 and CO2 groups (log rank test p=0.12). For the small RV group with intention to treat at birth, there was 71% survival at over 10 years for the CO1 group and 91% survival at over 10 years for CO2 group. There was significant difference in the survival between the CO1 and CO2 groups (log rank test p=0.03). No analysis was made for the unspecified hypoplasia as the numbers were too small. Conclusions: For both the antenatal small LV and small RV groups, the termination rate and compassionate care option remained unchanged between both cohorts. Overall, there has been improvement in the survival for the antenatal small LV and RV groups with intention to treat. This is likely due to improved perinatal management with detailed management plan and designated delivery at tertiary neonatal hospital close to the cardiac surgical centre, improved surgical expertise and experience, improved cardiac intensive care management as well as availability of ECMO for the sicker patients. In the antenatal small LV groups, although there has been improvement in survival, this is not yet statistically significant due to more complex patients with more co-morbidity being accepted for surgery. Whereas for the antenatal small RV groups, we see statistically significant improvement with survival reaching 90% at 10 years, due to increased use of non-surgical intervention like ductal stenting over conventional BT shunts which carry higher morbidity and mortality risk. Our survival outcomes are comparable with other published data across the world. Table 1